Kepemimpinan Transformatif dalam Perubahan Sosial era Demokrasi di Kota Jayapura - Abisay Rollo; Avelinus Lefaan; Ferry R. P. P. Sitorus; Sugeng Bayu Wahyono (JURNAL EKOLOGI BIROKRASI, 2025)
This study examines the role of transformational leadership in encouraging social participation and shaping the dynamics of social change in the democratic era, particularly within the community of Jayapura City. Transformational leadership is recognized as a leadership model that inspires followers, encourages active participation, and strengthens collective commitment toward shared goals. In democratic governance, this leadership approach is important because it facilitates collaboration between leaders and communities in addressing social challenges and promoting sustainable development. This research employs a qualitative case study approach to explore how transformational leadership influences community participation and social transformation in a multicultural urban society. Data were collected through field research methods, including in-depth interviews, observation, and document analysis, and were analyzed using descriptive qualitative techniques. The findings indicate that transformational leadership significantly strengthens social participation by fostering trust, encouraging dialogue, and empowering citizens to engage in community development initiatives. Leaders who adopt transformational practices are able to mobilize collective action and build social capital, thereby enhancing civic engagement and cooperation among diverse social groups. Moreover, transformational leadership plays a strategic role in managing social change by promoting inclusive governance, encouraging innovation, and strengthening community resilience amid social and political transformation. In the context of Jayapura City, the interaction between visionary leadership and community participation creates a dynamic environment that supports democratic development and social cohesion. Therefore, transformational leadership can be regarded as an important factor in facilitating constructive social change and strengthening participatory governance in contemporary democratic societies.